2020
DOI: 10.1186/s13660-020-02325-9
|View full text |Cite
|
Sign up to set email alerts
|

Fixed point theorems for sum operator with parameter

Abstract: This paper develops some new existence and uniqueness theorems of a fixed point for a class of sum operator equations with parameter λ 1 A(x, x) + λ 2 B(x, x) + λ 3 Cx + λ 4 Dx = x, where A, B are two mixed monotone operators, C is an increasing operator, D is a decreasing operator. In the case of positive parameters, the results obtained in this paper extend many existing conclusions in the field of study. Furthermore, by using the properties of Green's function and the above fixed point theorems of sum opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In the scientific literature, we only found one paper published in a repository (arXiv) where the author studied the first contagion outbreaks occurred in China until February 13, 2020 using Benford's Law [8]. This manuscript concluded that until this date, there was no evidence of alteration or manipulation of the cases registered in China.…”
Section: Introductionmentioning
confidence: 99%
“…In the scientific literature, we only found one paper published in a repository (arXiv) where the author studied the first contagion outbreaks occurred in China until February 13, 2020 using Benford's Law [8]. This manuscript concluded that until this date, there was no evidence of alteration or manipulation of the cases registered in China.…”
Section: Introductionmentioning
confidence: 99%